2016
DOI: 10.1363/48e8616
|View full text |Cite
|
Sign up to set email alerts
|

Abusive Experiences and Young Women's Sexual Health Outcomes: Is Condom Negotiation Self‐Efficacy a Mediator?

Abstract: CONTEXT Intimate partner violence and reproductive coercion are associated with unintended pregnancies and STDs. Greater condom negotiation self-efficacy among young women may mediate these associations. METHODS A sample of 841 female adolescents (aged 16–19) and 1,387 young adult women (aged 20–24) recruited from 24 family planning clinics in western Pennsylvania in 2011–2012 reported on intimate partner violence, reproductive coercion, condom negotiation self-efficacy and sexual health outcomes at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 60 publications
2
24
0
Order By: Relevance
“…Odds of UIP were also elevated among women who reported only RC or IPV (but not both). 31 In a separate study using the same sample, Jones et al 28 found that condom negotiation self-efficacy mediated the relationship between RC and past-year UIP among the young adult population (ages 20-24 years). In another study of women aged 18 or older, married or cohabitating Latina and Asian women, only those who experienced IPV, were twice as likely to experience a UIP relative to women who were not exposed to IPV.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Odds of UIP were also elevated among women who reported only RC or IPV (but not both). 31 In a separate study using the same sample, Jones et al 28 found that condom negotiation self-efficacy mediated the relationship between RC and past-year UIP among the young adult population (ages 20-24 years). In another study of women aged 18 or older, married or cohabitating Latina and Asian women, only those who experienced IPV, were twice as likely to experience a UIP relative to women who were not exposed to IPV.…”
Section: Introductionmentioning
confidence: 96%
“…24,25 In addition, emerging research has identified the role of behaviors of male partners in increasing women's odds of UIP. [26][27][28] Reproductive coercion (RC) is one such mecha-nism linking violence within intimate relationships and UIP. RC is a phenomenon that involves pregnancy coercion (e.g., using threats to promote a pregnancy) and active manipulation of condoms and hormonal contraception to promote a pregnancy (e.g., breaking condoms on purpose, flushing birth control pills down the toilet).…”
Section: Introductionmentioning
confidence: 99%
“…Significant health complications are associated with RC and IPV. These include gynecologic disorders (e.g., chronic pelvic pain and recurrent vaginal infections; ACOG, 2012), increased risk of sexually transmitted infections and HIV (Chamberlain & Levenson, 2010;Jones et al, 2016;Teitelman, Tennille, Bohinski, Jemmott, & Jemmott, 2011), pregnancy complications (e.g., vaginal bleeding, spontaneous abortion, and premature contractions;Han & Stewart, 2014), and unintended pregnancy (UIP; Han & Stewart, 2014;Nikolajski et al, 2015). In the United States, 45% of all pregnancies are unintended, and the highest rates of UIP occur in women between 18 and 24 years of age, women who are cohabitating but not married, women living in poverty, and Black and Hispanic women (Finer & Zolna, 2016).…”
mentioning
confidence: 99%
“…Ideas about how IPV could be linked to unintended pregnancy via pregnancy coercion or contraceptive sabotage have been in the research literature since the 1990s (Campbell et al 1995; Wingood and DiClemente 2000), but the studies that empirically examine the link have been cross-sectional, small, or based on samples from clinics or domestic violence shelters (Berenson, San Miguel, and Wilkinson 1992; de Bocanegra et al 2010; Center for Impact Research 2000; Jones et al 2016; Miller et al 2007; Miller et al 2010; Moore, Frohwirth, and Miller 2010; Williams, Larsen, and McCloskey 2008). Our contribution is to pay special attention to the timing of IPV and pregnancy—recent violence, past violence in this relationship, and violence in prior relationships—and to investigate the extent to which reproductive coercion accounts for any links between IPV and subsequent pregnancy.…”
mentioning
confidence: 99%